PENGARUH KEPERCAYAAN, KEAMANAN, PERSEPSI RISIKO, SERTA KESADARAN NASABAH TERHADAP ADOPSI E-BANKING DI BANK BRI KANTOR KAS UNIVERSITAS ISLAM MALANG - Ani Luluk Mauludiyah; Nur Diana (Universitas Islam Malang, 2018)
ABSTRACTThis study was conducted in order to determine the effect of trust, security,risk perception, as well as customer awareness towards the adoption of e-bankingat Bank BRI Malang Islamic University Cash Office. The selected type of researchis quantitative study using a sample of customers. Results from this study showedthat variables significantly confidence or positive effect on the adoption of ebanking. While the security and risk perception variables do not significantly oradversely adoption of e-banking. And the awareness variable influencesignificantly or positively impact the adoption of e-banking. According to thisresearch, we can see that the trust and awareness is the main factor of customerschoosing to use e-banking in the transaction.Keywords: Confidence, security, risk perception, awareness, adoption, e-banking